Proceedings of the 2019 1st International Conference on Engineering and Management in Industrial System (ICOEMIS 2019) 2019
DOI: 10.2991/icoemis-19.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Job Evaluation Methods: Implications for the Salaries Design in Publishing Company

Abstract: Job evaluation is an crucial factor in compensation design because it relates to issues of equity and worker satisfaction. Case study at the Human Resources Department of a publishing company show that there is a problem with the compensation system that is felt to be unfair. The existing method used in the company was job classification without considering workload. Therefore, it is important to determine the job relative value as a reference for designing compensation. This study compared two job evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, the addition of the PMJEQ bolstered confidence in the decision. The combination of job analysis and job evaluation methods has been employed elsewhere, for example, Suwarsono et al (2019) compared two different job evaluation (and job analysis) techniques in designing a pay structure. The results of their study indicated that each job evaluation produced different job clusters, that is, unique pay structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the addition of the PMJEQ bolstered confidence in the decision. The combination of job analysis and job evaluation methods has been employed elsewhere, for example, Suwarsono et al (2019) compared two different job evaluation (and job analysis) techniques in designing a pay structure. The results of their study indicated that each job evaluation produced different job clusters, that is, unique pay structures.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the “worth” of jobs is notoriously difficult, and this is true whether one looks within organizations, across organizations, within industries, or more globally (Hilling, 2020; Guppy & Vincent, 2021; Treiman & Hartmann, 1981). Organizations have often relied on ranking or classifications of jobs, with many efforts—especially in previous decades—to use point factor or factor comparison methods of job evaluation (Belcher & Atchison, 1987; Risher, 2013; Suwarsono et al, 2019). Concerns arise when non-work-related factors, such as gender, race, or age, appear to be related to pay disparities, either within job categories, or across jobs that appear (in some fashion) to be similar (Flores et al, 2021).…”
mentioning
confidence: 99%
“…The findings will assist organizations in making informed decisions related to job design, performance management, and compensation. Suwarsono et al compares and evaluated different job evaluation methods, such as the ranking method, classification method, and point factor method, specifically in the context of production roles in the manufacturing industry [1]. It assesses the strengths and weaknesses of each method and provides insights into their practical application and effectiveness.…”
Section: Literature Surveymentioning
confidence: 99%